Dragon lords : the history and legends of Viking England - Parker, Eleanor Catherine, 1986- (London : Bloomsbury Academic, 2019)
"Why did the Vikings sail to England? Were they indiscriminate raiders, motivated solely by bloodlust and plunder? One narrative, the stereotypical one, might have it so. But locked away in the buried history of the British Isles are other, far richer and more nuanced, stories; and these hidden tales paint a picture very different from the ferocious pillagers of popular repute"--
Introduction -- 'From the north comes all that is evil': Vikings, kings and saints, c.985-1100 -- The sons of Ragnar Lothbrok -- The story of Siward -- Danish sovereignty and the right to rule -- 'Over the salt sea to England': Havelok and the Danes -- Epilogue: The Danes in English folklore.
Lisäpainokset: Paperback edition 2021.
Lisäpainokset: Paperback ed. 2021.
Sisältää bibliografisia viitteitä ja hakemiston.
Keywords: Vikings -- England -- History; viikingit; historia; kirjallisuus; keskiaika; kansanperinne; kansantarinat; paikannimet; paikallishistoria (historia); Englanti; Iso-Britannia.; Great Britain -- History -- Anglo-Saxon period, 449-1066.